A comparative assessment of chemical, mechanical, and thermal characteristics of treated oil palm/pineapple fiber/bio phenolic composites. Issue 4 (8th February 2022) - Awad, Sameer A.; Jawaid, Mohammad; Fouad, Hassan; Saba, Naheed; Dhakal, Hom Nath; Alothman, Othman Y.; Khalaf, Eman M.
Abstract: In this study, the alkali‐treated and untreated hybrid fibers incorporated with bio phenolic matrix to enhance the chemical interactions, mechanical and thermal properties have been investigated. The oil palm fiber (OPF) and pineapple fiber (PALF) were utilized as reinforcements into bio phenolic resin. The improvements in chemical interactions were monitored by the Fourier transform infrared spectrometer. The modifications of the surface for hybrid natural fibers (OPF/PALF) were enhanced in comparison to pure fiber composites. The composites' dynamic mechanical behavior such as storage modulus, loss modulus, and damping properties were also investigated by dynamic mechanical analysis. Thermogravimetric analysis analyzed the performance of untreated (OPF and PALF) and treated (OPF/OPF) composites at elevated temperature and observed adequate interfacial bonding as a result of the improvements in thermal stability. The results presented that alkali) NaOH(incorporation in hybrid composites (OPF/PALF) results in increased the tensile strength and modulus among all composites. Furthermore, the tensile strength and modulus improved to the maximum value for treated 50% PALF composite compared to other composites. The hybridisation of treated alkali (5% NaOH/50% PALF) fiber shows best performance on tensile strength and modulus with 33.3 and 7535.2 MPa, respectively compared to other composites. The alkali‐treated hybrid composites (NaOH/1OPF.1PALF) exhibited the greatest flexural strength (99.8 MPa) and modulus (8813.1 MPa). The enhancement of the interfacial adhesion between pure and hybrid fiber composites and bio phenolic matrix through the mercerisation of OPF and PALF fibers reinforced composite played an essential role in improving the mechanical properties of composites via alkali treatment with NaOH solution. Natural fiber reinforced composites are commercially attractive for high‐volume applications; while their properties can be improved by adding alkali solution as stabilizers. It can be recommended from the findings of this study that the alkali treatment (5% NaOH) can be used to enhance the efficiency of agriculture waste biomass. Additionally, the hybridization of bio‐fiber composites has potential to develop novel type of biodegradable and sustainable composites suitable for various industrial and engineering applications. Abstract : FTIR spectra of treated and untreated fiber composites.